2005
DOI: 10.1038/sj.onc.1208498
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signature of retinoic acid treatment in acute promyelocytic leukemia

Abstract: Acute promyelocytic leukemia (APL) is a distinct subtype of acute myeloid leukemia characterized by a block of differentiation at the promyelocytic stage. APL patients respond to pharmacological concentrations of all-trans retinoic acid ( RA) and disease remission correlates with terminal differentiation of leukemic blasts. The PML/RAR oncogenic transcription factor is responsible for both the pathogenesis of APL and for its sensitivity to RA. In order to identify physiological targets of RA therapy, we analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 37 publications
8
41
1
1
Order By: Relevance
“…Previous studies have shown the activation of NF-kB upon ATRA-induced maturation of APL (Mathieu et al, 2005) and enrichment for NFkB binding sites in RA target genes has been described (Meani et al, 2005). To investigate whether ATRAinduced NF-kB activation regulates miRNAs, we cotransfected NB4 cells with a potent NF-kB inhibitor expression plasmid (IkBa-SR) or empty vector and treated the cells with ATRA or dimethylsulphoxide (DMSO) (control).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown the activation of NF-kB upon ATRA-induced maturation of APL (Mathieu et al, 2005) and enrichment for NFkB binding sites in RA target genes has been described (Meani et al, 2005). To investigate whether ATRAinduced NF-kB activation regulates miRNAs, we cotransfected NB4 cells with a potent NF-kB inhibitor expression plasmid (IkBa-SR) or empty vector and treated the cells with ATRA or dimethylsulphoxide (DMSO) (control).…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA was extracted from U937 cells transduced with shPIR 7 or with the empty pSICO-R vector and hybridized to Affymetrix GeneChip HG-U133 Plus 2.0 arrays as described in Materials and methods. Results were analyzed as previously Pirin downregulation in AML S Licciulli et al described, 3,18 and regulated genes (more than twofold) were annotated and classified using the Ingenuity pathways analysis software. A total of 492 regulated genes were identified, 305 induced and 187 repressed, after knockdown of PIR protein (Supplementary Table 2).…”
Section: Pirin (Pir) Knockdown In U937 Cells Results In Increased Expmentioning
confidence: 99%
“…PML-RARa is a potent and specific activator of c-fos promoter By gene array, PML-RARa upregulates 1569 and downregulates another 1726 genes (Alcalay et al, 2003;Park et al, 2003;Nouzova et al, 2004;Meani et al, 2005). Examples of repressed genes are RARb2 and C/EBPb (Di Croce et al, 2002;Duprez et al, 2003), while examples of induced genes are Cyclin A1, p21 and c-fos (Casini and Pelicci, 1999;Mu¨ller et al, 2000;Alcalay et al, 2003;Meani et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Examples of repressed genes are RARb2 and C/EBPb (Di Croce et al, 2002;Duprez et al, 2003), while examples of induced genes are Cyclin A1, p21 and c-fos (Casini and Pelicci, 1999;Mu¨ller et al, 2000;Alcalay et al, 2003;Meani et al, 2005). Given that c-fos gene is involved in proliferation, we hypothesized that part of the function of PML-RARa may be to directly promote cellular growth via transcriptional regulation of c-fos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation